HR-LCMS-Based Metabolite Profiling, Antioxidant, and Anticancer Properties of Teucrium polium L. Methanolic Extract: Computational and In Vitro Study - Noumi, Emira (Antioxidants (Basel), 2020)
In this study, we investigate the phytochemical profile, anticancer, and antioxidant activities of Teucrium polium methanolic extract using both in vitro and in silico approaches. The results showed the identification of 29 phytochemical compounds belonging to 13 classes of compounds and 20 tripeptides using High Resolution-Liquid Chromatography Mass Spectrometry (HR-LCMS). 13R-hydroxy-9E,11Z octadecadienoic acid, dihydrosamidin, valtratum, and cepharantine were the main compounds identified. The tested extract showed promising antioxidant activities (ABTS-IC(50) = 0.042 mg/mL; 1,1-diphenyl-2-picrylhydrazyl (DPPH)-IC(50) = 0.087 mg/mL, β-carotene-IC(50) = 0.101 mg/mL and FRAP-IC(50) = 0.292 mg/mL). Using both malignant Walker 256/B and MatLyLu cell lines, T. polium methanolic extract showed a dose/time-dependent antitumor activity. The molecular docking approach revealed that most of the identified molecules were specifically binding with human peroxiredoxin 5, human androgen, and human progesterone receptors with high binding affinity scores. The obtained results confirmed that T. polium is a rich source of bioactive molecules with antioxidant and antitumor potential.